Quantitative Analysis of Mineral in Seawater Concentrate from Pamekasan, Madura Using XRF and ICP-OES Methods - Hartesi, Barmi; Wardhana, Yoga Windu; Muhaimin, Muhaimin; Sriwidodo, Sriwidodo; Khairinisa, Miski Aghnia; Dewi, Mayang Kusuma; Chaerunisaa, Anis Yohana (Journal of The Indonesian Society of Integrated Chemistry, 2024)
Seawater concentrate from Pamekasan is a product with high mineral content. The mineral content analysis of Pamekasan seawater concentrate was conducted using a comparative test of results from X-Ray Fluorescence Spectrometry (XRF) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). This mineral content testing used a skin moisture device. The essential minerals found in Pamekasan seawater concentrate through analysis are Mg, Cl, K, Ca, Cr, Mn, Cu, and Zn. Statistical analysis results from XRF and ICP-OES on market products showed no significant difference in average results; however, there was a significant difference in average results in the samples. The most recommended method for analyzing seawater mineral concentrate from Pamekasan is ICP-OES due to its wider detection range and lower matrix interference.